AGE OF THE INITIATION OF MINUSA BASINS, SOUTHERN SIBERIA - Babin G.A.; Vladimirov A.G.; Kruk N.N.; Gibsher A.S.; Sovetov Yu.K.; Sergeev S.A.; Sennikov N.V. (My University, 2004)
The volume and structural setting of the Byskar Group indicate that the initiation of Minusa basins and, hence, the maximum impact of plume source on the Siberian continent margin should be referred to the Lochkovian and Pragian ages of Early Devonian according to the International Stratigraphic Chart. At the same time, the data obtained by no means imply that the East Sayan and adjacent regions are completely devoid of Ordovician and Silurian volcanic sequences. The recent geological, isotopic geochronological, and paleomagnetic data confirm the extensive development of Ordovician subalkaline volcanic complexes in this territory. However, it is obvious now that the volcanic sequences of reliable Ordovician age have nothing to do with the Byskar Group and must be regarded as self-dependent stratons denoted by their own names.